Global, regional, and national trends in decubitus ulcer burden from 1990 to 2021 and forecasts to 2040 - Ruijuan Li; Xueneng Yang; Hanbo Chen; Minglin Dong; Jun Shu; Junfei Liu; Ming Zeng (Frontiers in Public Health, 2025)
BackgroundDecubitus ulcers, or pressure injuries, are a growing global health issue, particularly among aging populations. However, comprehensive studies on their burden and trends remain limited.MethodsUsing the GBD 2021 database, we analyzed global, regional, and national burdens of decubitus ulcers from 1990 to 2021, including prevalence, incidence, DALYs, and death. Key metrics were assessed through age-standardized rates and absolute counts. Statistical methods such as decomposition analysis and Bayesian age-period-cohort modeling were employed to explore trends and disparities. Future projections were made up to 2040.ResultsWhile age-standardized prevalence and incidence rates remained stable, DALY and death rates declined globally. Nevertheless, absolute cases, DALYs, and deaths increased significantly, driven by population aging and growth. High-SDI regions showed higher prevalence but lower DALY and death burdens, while low-SDI regions faced severe challenges due to limited resources. Health inequalities persisted, with widening absolute disparities despite narrowing relative inequalities. By 2040, total burden is projected to rise, especially among individuals over 40.ConclusionThe increasing global burden of decubitus ulcers highlights the need for tailored prevention strategies and resource allocation. These findings offer critical evidence for reducing health disparities and improving global management of this condition.